ANALISIS NILAI MECHANICAL PROPERTIES GAS TUNGSTEN ARC WELDING (GTAW) PADA MATERIAL STAINLESS STEEL 304 DENGAN VARIASI HEAT INPUT MENGGUNAKAN METODE NDT - Widodo, Agus; Rivandi, Merdieco; Prasetiyo, Joko (Politeknik META Industri Cikarang, 2023)
ABSTRACTPT. XYZ is a company engaged in industrial gas, gas installation, tank / iso tank service, and various kinds of equipment related to industrial gas. Based on the source of the report data from thesection, workshop there is a fabrication process for industrial gas installations which often occurs in defects in the welding process which often results in failure in welding tests. The cause of welding defects can be due to incorrect welding procedures, inadequate preparation and can also be caused by equipment and consumables that do not meet standards. So, based on this, a research with the title.